2015
DOI: 10.1111/pce.12580
|View full text |Cite
|
Sign up to set email alerts
|

New prenyllipid metabolites identified in Arabidopsis during photo‐oxidative stress

Abstract: In the present study, we have identified new prenyllipid metabolites formed during high light stress in Arabidopsis thaliana, whose origin and function remained unknown so far. It was found that plastoquinone-C accumulates mainly in the reduced form under high light conditions, as well as during short-term excess light illumination both in the wild-type and tocopherol biosynthetic vte1 mutant, suggesting that plastoquinone-C, a singlet oxygen-derived prenyllipid, is reduced in chloroplasts by photosystem II or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Enhanced gene expression was found for TYROSINE AMINO-TRANSFERASE1 and 4-HYDROXYPHENYLPYRUVATE DIOXYGENASE, which are involved in homogentisate biosynthesis for PQ and tocopherols; SOLANESYL DI-PHOSPHATE SYNTHASE1 (SPS1) and SPS2, which provide isoprenoid side chains for ubiquinone and PQ; and VTE1 and VTE4, which are involved in tocopherol and plastochromanol biosynthesis. Increased accumulation of a-tocopherol, reduced PQ (PQH 2 ), and plastochromanol, all of which can serve as antioxidants, have been reported in Arabidopsis leaves under HL (Dłu _ zewska et al, 2015). We also found up-regulation of two phylloquinone (vitamin K 1 ) biosynthetic genes, PHYLLO and ABERRANT CHLOROPLAST DEVEL-OPMENT4, in Mature-EOD (Fig.…”
Section: Differentially Regulated Genes In Pigment and Prenylquinone supporting
confidence: 63%
“…Enhanced gene expression was found for TYROSINE AMINO-TRANSFERASE1 and 4-HYDROXYPHENYLPYRUVATE DIOXYGENASE, which are involved in homogentisate biosynthesis for PQ and tocopherols; SOLANESYL DI-PHOSPHATE SYNTHASE1 (SPS1) and SPS2, which provide isoprenoid side chains for ubiquinone and PQ; and VTE1 and VTE4, which are involved in tocopherol and plastochromanol biosynthesis. Increased accumulation of a-tocopherol, reduced PQ (PQH 2 ), and plastochromanol, all of which can serve as antioxidants, have been reported in Arabidopsis leaves under HL (Dłu _ zewska et al, 2015). We also found up-regulation of two phylloquinone (vitamin K 1 ) biosynthetic genes, PHYLLO and ABERRANT CHLOROPLAST DEVEL-OPMENT4, in Mature-EOD (Fig.…”
Section: Differentially Regulated Genes In Pigment and Prenylquinone supporting
confidence: 63%
“…Future study will include elucidation of how PQ lipids or slr2103 contributes to the acclimatization, including whether it acts directly or indirectly. Although PQ-B has long been recognized in plants as a minor lipid component, information on its physiological roles is limited, including the possible electron acceptor from PSII and its quantitative increase with age in A. thaliana when grown under high light conditions ( Kruk et al., 1998 ; Dłużewska et al., 2015 ). The indispensable roles of PQ lipids including PQ-B in cyanobacterial NaCl-acclimatization would facilitate reexamination of the physiological roles of PQ-B in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, it is unlikely that PQ-B contributes to the physiological processes in seed plants in a similar manner to that in cyanobacteria observed under statically culturing conditions ( Figure 5 ). It is of note that PQ-B in seed plants accepted electrons from PSII or increased in quantity during cultivation at a high light intensity [ 4 , 5 ], which might raise the possibility that PQ-B is involved in their acclimatization to the high-light stress. A mutant deficient in PQ lipids in Synechococystis 6803 or Synechococcus 7002 would be a powerful tool to comprehensively understand the physiological significance of PQ lipids in cyanobacteria, possibly including those in high-light stress acclimatization.…”
Section: Discussionmentioning
confidence: 99%
“…The study of seed plant PQ-B from physiological aspects has previously demonstrated its potential to function as an electron acceptor of PSII in tobacco thylakoid membranes and its quantitative increase in A. thaliana plants with aging during growth under high light Microorganisms 2023, 11, 1177 2 of 14 conditions [4,5]. However, no conclusion has been drawn concerning the physiological roles of PQ-B in seed plants, PQ-B deficient mutants of which are unavailable, with no genes identified for PQ-B synthesis.…”
Section: Introductionmentioning
confidence: 99%